EFEITO DO MÉTODO PILATES COMO TRATMENTO ADJUVANTE EM PACIENTES PORTADORES DE FIBROMIALGIA - Amorim, Nelbe Maria Ferreira de (2009)
Fibromyalgia is a complex multifactorial disorder characterized by chronic pain associated with fatigue, depression, anxiety, alterations in sleep patterns and cognition. Aerobic exercise and training of progressive strength are proposed as treatments of the symptoms. The Pilates method is proposed to improve the flexibility of the body, to emphasize the strengthening of the trunk of the body and posture. The aim of this clinical assay was to evaluate the Pilates method on the daily activities of patients with fibromyalgia, on pain, on the number of tender points and on the amplitude of movement of the shoulders and hips, measured respectively by a Fibromyalgia Impact Questionnaire (FIQ), by the Visual Analogical Scale (VAS), by fingerpressure and by photogrammetry. Thirty eight women with a diagnosis of fibromyalgia were randomly distributed into two groups. Group 01 (G1 n=19) were submitted to a program of Pilates based-exercise, two times per week for 8 consecutive weeks with each session lasting sixty minutes and there was also an educational program. Group 2 (G2 n=19) the control group, were only submitted to the educational program. The evaluations were made in both groups at the beginning and at the end of the program. Statistical significance were found in the fibromyalgia impact on daily life (p=0,014), on pain (p=0,0004), on the number of tender points (p=0,012). The amplitude of movements of the shoulders and hips had no significant results. It s therefore concluded that in this study, the Pilates method was efficient in reducing the fibromyalgia impact on daily life, on the pain intensity and in the number of tenders points, and it was not efficient in gaining amplitude of movement in the shoulders and hips.